Myths and realities of the Ukrainian-Bulgarian educational ties (the 60-80s of the ХХ century) - Halyna Dokashenko (Cхід)
The article deals with the basic characteristics of the Ukrainian-Bulgarian mutual relations in the sphere of education - a key role of the ruling communist parties, a constant and comprehensive control etc. At the same time the author proves the objective conformity to strengthening of integration processes in the development of the educational sphere.